Poetry Guided Speaking - Ali, Shaukat; Nawib, Abdullah Mohd; Rajab, Azizah (International Journal of Engineering and Technology, 2018)
This study compares the effect of traditional teaching materials exploited for teaching speaking skills in Pakistani universities and poetry guided speaking (PGS) materials on the overall speaking skill and speaking sub-skills of ESL (English as a second language) learners. The study was a quasi-experimental one having two intact groups; a control group (CG) and an experimental group (EG). Total number of respondents was 77,38 inCG and39 inEG. Both the groups were first year students from the faculty of biological sciences, University of Malakand, Pakistan. The age of the respondents varied from 19 to 21. CG was taught speaking skills through traditional teaching materials whereas EG was extended PGS as teaching materials for speaking skills. Pre-tests and post-tests were conducted to measure the effect of the different kinds of teaching materials on the overall speaking skill and its four sub-skills including pragmatic competence, discourse competence, fluency and grammatical competence. T-tests were applied to compare the performance of the control and experimental groups. The results of the study indicated that PGS materials were more effective in teaching speaking skills than the traditional teaching materials. The study suggests that PGS maybe be utilized to teach speaking skills in Pakistani universities.